ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF SOME TRANSITION METAL COMPLEXES OF TWO LIGANDS DERIVED FROM AMINO ACIDS AND 2 – IMINO – 1 – METHYLIMIDAZOLIDIN – 4 – ONE - Manir, Muhammad; NURA SULEIMAN GWARAM; Usman Ahmad Madaki (FUDMA JOURNAL OF SCIENCES, 2022)
Plant extracts are most of the time used for antioxidant and antimicrobial studies. The Present study was designed to evaluate the activity of metal complexes as antioxidant and against some selected bacterial and fungal isolates. The new metal complexes of Cr (III) and Zn (II) containing ligands derived from Tyrosine, Leucine and 2 – imino – 1 – methylimidazolidin – 4 - one were selected. The test compounds were evaluated for their possible antioxidant activity through free radical scavenging activity via using 1,1 – diphenyl – 2 – picryl – hydrazyl (DPPH) method. All the complexes exhibited good to moderate activity with Cr (III) complex (CrL1) and (CrL2) as the best radical scavengers having the % inhibition value of 67.74 and 65.33 respectively. The complexes were also screened for their antimicrobial activities against two bacterial isolates and one fungal isolate (Streptococcus pneumoniae, Klebsiella pneumoniae and Aspergillus niger). The result showed that all the compounds have the moderate activity against the tested organisms.